COMPARISON OF RADIAL ARM MAZE ANDMORRIS WATER MAZE FOR EVALUATION OFSPATIAL MEMORY IN EXPERIMENTAL ANIMALS DURING NEUROBEHAVIORAL TESTING - ALEKSANDR M. Iptyshev; YANA V. Gorina; OLGA L. Lopatina; YULIYA K. Komleva; ANATOLIY I. Chernykh; OLGA A. Belova; ALLA B. Salmina (Фундаментальная и клиническая медицина)
Rodents are widely used for the evaluation of the spatial memory due to inherited predisposition and relatively easy training. A number of mazes have been successfully developed and used, with Morris water maze and eight-arm radial maze being two the most appropriate. In this review, we compare advantages and shortcomings of these two tests.